Nerve strain correlates with structural changes quantified by fourier analysis. Issue 3 (27th July 2013) - Love, James M.; Chuang, Ting‐Hsien; Lieber, Richard L.; Shah, Sameer B.
ABSTRACT Introduction: Nerve deformation affects physiological function. Bands of Fontana are an optical manifestation of axonal undulations and may provide a structural indicator of nerve strain. Methods: We developed an automated Fourier‐based image processing method to quantify the periodicity of bands of Fontana both in bright field images and in axonal undulations in immunolabeled longitudinal sections. Results: We found a strong linear relationship between applied strain and the frequency of bands of Fontana in rat sciatic nerves (−0.0056 μm−⋅%−, r2 = 0.829; P < 0.05). This relationship agreed with the observed trend between strain and axonal waviness, calculated from longitudinal sections of sciatic nerves immunolabeled against myelin basic protein. Conclusions: This accurate and objective approach has potential to increase our understanding of structure–function relationships in the nervous system and to guide preservation and enhancement of neural function. Muscle Nerve48: 433–435, 2013